With The Motivation Of Dental Medication In The New Normal Era Pidie District Tangse Puskesmas - Hibrati; Safriana; Nurlaili; Fittrizal; Suryani; Teuku Salfiyadi (Journal Dental Health, 2022)
Background: The high average prevalence of malnutrition and infectious diseases is exacerbated by issues related to inequality and the low quality of public health services. Many people may feel afraid to have their teeth checked during the Covid-19 pandemic. Research Title: Relationship between Perception of Risk of Infecting with Covid and Motivation for Dental Treatment in the New Normal Era at Tangse Health Center. The purpose of the study: is to find out whether there is a relationship between the perceived risk of contracting Covid-19 with the motivation to seek dental treatment in the new normal era at the Tangse Health Center. Research method: The research method used is chie square. Research sample: The dental clinic visitors from January to July 2022 were 98 people. Research results: Based on the results of the Chi-Square test using the SPSS program, it was obtained that P-value = 0.001, (<0.05) Smaller than a = 0.05, which means that there is a significant relationship between the perception of contracting COVID with the motivation to seek dentistry in Indonesia. the new normal era at Tangse Health Center. Conclusion: There are 63 people (64.3%) who have a low-risk perception of covid-19 and 68 people (69.4%) have low motivation to go to a dental clinic and based on the chie square test there is a significant relationship between the perception of the risk of contracting covid with the motivation for dental treatment, it means that students who are afraid of contracting COVID-19 have low motivation to seek dental treatment.